2020
DOI: 10.1299/transjsme.20-00323
|View full text |Cite
|
Sign up to set email alerts
|

Influence on surface characteristics generated in Low Frequency Vibration Cutting

Abstract: LFV is one of effective machining technologies to break long and continuous chips in the turning process. LFV technology stands for low frequency vibration cutting. Vibration in the tool feed direction is applied in LFV and it is synchronously controlled with the spindle rotation. When the machined surface is focused on, characteristic surface patterns are formed in LFV turning process because of the tool vibration in feed direction. In this paper, a simulation technique to visualize the surface profile genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Furthermore, vibration conditions were reported to influence the texture of machined surfaces (Okamura et al, 2006). Miyake et al (2020) confirmed that adjusting the amplitude ratio influences the surface roughness, which can be improved by changing the trajectory of the tool as the parameter is optimized (Miyake et al, 2020).…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations
“…Furthermore, vibration conditions were reported to influence the texture of machined surfaces (Okamura et al, 2006). Miyake et al (2020) confirmed that adjusting the amplitude ratio influences the surface roughness, which can be improved by changing the trajectory of the tool as the parameter is optimized (Miyake et al, 2020).…”
Section: Introductionmentioning
confidence: 82%
“…Simulations were utilized to demonstrate the machined surface properties by plotting the tool trajectory based on the tool nose R, frequency ratio, and amplitude ratio (Miyake et al, 2020). The tool path can be calculated as follows:…”
Section: Surface Topography By Low-frequency Vibration Cuttingmentioning
confidence: 99%
See 2 more Smart Citations